Defending the French language: an online battle? - Humphries, Emma (2017)
This study investigates the metalinguistic discourse of Twitter users in the French language. It is often claimed that France is a country in which standard language ideology and prescriptivism are deeply entrenched. In modern society, the internet seems to have become a popular space to share and enforce prescriptive ideas about ‘correct’ and ‘incorrect’ language. Given suggestions that the views expressed online are often more extreme than offline interactions, the internet, in this case Twitter, is a particularly interesting context for a study of metalinguistic discourse. Through analysis of a corpus of tweets, created using search terms such as orthographe and the non-standard verb form croivent, I investigate attitudes towards both usages which deviate from the prescribed norm and the speakers behind the deviations. The results show that Twitter users have clear ideas about what constitutes ‘acceptable’ and ‘unacceptable’ language, and equate non-standard usages with low intelligence and status. There has been relatively little research on contemporary prescriptivism in France and computer-mediated communication in French has also attracted little interest to date. This study uses innovative research methods to provide the first analysis of contemporary French prescriptivism in action in the online sphere.